Fundamentals of electrochemical science - Oldham, Keith B. (Academic Press, 1994)
"[Fundamentals of Electrochemical Science] is a valuable contribution and I support the publication ... I am looking forward to seeing this book on the shelves, and once published, I will not hesitate to recommend itto my students."--ANDRZEJ WIECKOWSKI, University of Illinois at Urbana-Champaign Key Features * Deals comprehensively with the basic science of electrochemistry * Treats electrochemistry as a discipline in its own right and not as a branch of physical or analytical chemistry * Provides a thorough and quantitative description of electrochemical fundamentals